PENGARUH PEMBERIAN INSENTIF, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA SIDOARJO UTARA - Achmad Sholihin (MAPAN: Jurnal Manajemen Akuntansi Palapa Nusantara, 2016)
This study aims to identify and analyze influence of incentives, motivation and leadership to employee performance, and analyze one of the variable incentive, motivation and leadership that has dominant influence on employee performance.This study uses simple method of saturation, where the number of samples used the same amount as the total population. While the number of samples taken as many as 42 employees in the Tax Office Pratama in North Sidoarjo. Further data processing performed by using regression analysis (multiple regression analysis), and test the hypothesis using the F-test and t-test. The results of this study indicate that the incentive variable (X1), work motivation (X2), and leadership (X3) has positive and significant impact on employee performance Tax Office Pratama in North Sidoarjo. Where as the dominant influence work motivation (most influential) and significant to employee performance the Tax Office Pratama in North Sidoarjo, with analysis of the standardized coefficients (Beta) = 0.624. Means each of the independent variables is relationship that can change and improve employee performance with reasonably well in providing services to the community